Triggerfish twist eaudiobook Serge storms series, book 4. - Dorsey, Tim (Serge Storms, 2013)
Ensconced in a lovely tropical villa on idyllic Triggerfish Lane, Jim Davenport anticipates the good life to come. But this isn't living-it's Florida-and the neighborhood is not quite what it seems. It's got overly aggressive Little League parents, drug-free Rastafarians, homicidal hookers, unnatural sex and casual violence. Oh, yes, and there's a psychopathic serial killer-cum-Sunshine-State folklorist named Serge A. Storms living directly across the street. So it's only a matter of time before Jim up and actually kills somebody . "Imagine the violence of Edna Buchanan married to the skewed worldview of Dave Barry; now you're ready to meet Tim Dorsey."-Booklist "Triggerfish Twist makes for twisted fun . a must-read book on this summer's list."-Tampa Tribune